1995
DOI: 10.1093/gerona/50a.4.m227
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Activity of the Human Natural Anti-Gal Antibody in Young and Elderly Populations

Abstract: The proportion of individuals with low affinity anti-Gal increases in the elderly population in comparison with the young population. The possible molecular mechanisms which may result in the age-associated decrease in the antibody affinity are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 0 publications
2
23
1
Order By: Relevance
“…A further advantage for clinical application of this approach is the fact that all humans have natural antibodies against the Gal(␣1,3)Gal epitope, although the proportion of individuals with low affinity anti-Gal antibody increases in the elderly. 28 Immunisation with the sugar epitope is a possible way to increase titres of anti-Gal antibodies if this poses a limitation.…”
Section: Figure 6 Pi-plc Digestion Of Target Cells Ht1080␣ and Nontrmentioning
confidence: 99%
“…A further advantage for clinical application of this approach is the fact that all humans have natural antibodies against the Gal(␣1,3)Gal epitope, although the proportion of individuals with low affinity anti-Gal antibody increases in the elderly. 28 Immunisation with the sugar epitope is a possible way to increase titres of anti-Gal antibodies if this poses a limitation.…”
Section: Figure 6 Pi-plc Digestion Of Target Cells Ht1080␣ and Nontrmentioning
confidence: 99%
“…It constitutes ~1% of serum Igs in all young and elderly individuals that are not severely immunocompromised (15, 16). Anti-Gal Ab production is elicited as a result of constant antigenic stimulation by gastrointestinal bacteria (17).…”
mentioning
confidence: 99%
“…We speculated that the complement activation level was the main factor underlying differences in cell death among different ␣-gal-expressing cells. The activation of the complement cascade mediated by ␣-gal is affected by ␣-gal density on the targeted cells, blood type, anti-␣-gal Ab titers, and concentration of complement factors (35,41,63,67). In our study, the Ls-174T-GT, with a higher level of ␣-gal expression than SW620-GT, showed significantly lower sensitivity to CDC compared with SW620-GT.…”
Section: Discussionmentioning
confidence: 99%